Pituitary Macroadenoma Treated with Cabergoline: the Role of Neuro-Ophthalmic Examination in Diagnosis and Follow Up Management - Yunita Latif Lote; Batari T Umar; Yunita Mansyur (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To describe the importance of neuro-ophthalmic examination on pituitary macroadenomapatient with bitemporal hemianopia and treated with cabergoline.Case Illustration: A 50-year-old female came with blurry vision on both eyes. She had 20/40 and 20/30vision right eye and left eye respectively, no RAPD, no limitation of gaze, anterior and posterior segmentswere unremarkable. She had superior bitemporal defect expanding to inferior quadrant of visual fieldby Humphrey. MRI scan showed suggestive pituitary macroadenoma with bleeding and supression tosuperior chiasm. The prolactin level was elevated and she was then referred to endocrinologist andgiven dopamine agonist (cabergoline) treatment. Six months after cabergoline therapy, patient’s visualacuity had improved to 20/25 on both eyes, no progression on Humphrey visual field defect and alterationin size of the macroadenoma from MRI.Conclusion: A characteristic visual field defect can be a first sign for pituitary macroadenoma. Surgicalare not always necessary. Medicine therapy can be beneficial for secreting pituitary macroadenoma.Ophthalmology examination can help assessing the prognosis of the disease.Keywords: bitemporal hemianopia, pituitary macroadenoma, prolacin, cabergoline